2019
DOI: 10.35940/ijitee.l3709.119119
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality in Non-Communicable diseases

Abstract: Virtual Reality (VR) is often associated with the gaming business, the advancement isn't just about gaming. Increased reality has been around for quite a while now and there have been new VR applications in different fields. It is ordinary that in excess of 500 million VR headsets will be sold always 2025 and the entire VR development would be worth over $30 billion consistently 2020. This gigantic advancement can't be solely from the gaming business, anyway, accounts from various industry zones which are viab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Studies have shown that VR can positively affect physical symptoms such as pain, blood pressure, heart rate, respiratory conditions (Condon et al, 2020; Eijlers et al, 2019; Ioannou et al, 2020; Keshvari et al, 2021; Smith et al, 2020) and psychological symptoms such as anxiety, fear, and stress (Kim et al, 2021; Smith et al, 2020; Vieira et al, 2018). In recent years, in the cardiovascular area, VR has come into use in instruction, pre‐procedural arranging, in‐procedural representation, and the adoption of healthy lifestyle behaviors after the diagnosis of CVDs (Singla & Senthil Kumar, 2019). A relatively new technology, VR is now also used in cardiac rehabilitation programs to improve health behavior and clinical outcomes, motivation, and commitment (García‐Bravo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that VR can positively affect physical symptoms such as pain, blood pressure, heart rate, respiratory conditions (Condon et al, 2020; Eijlers et al, 2019; Ioannou et al, 2020; Keshvari et al, 2021; Smith et al, 2020) and psychological symptoms such as anxiety, fear, and stress (Kim et al, 2021; Smith et al, 2020; Vieira et al, 2018). In recent years, in the cardiovascular area, VR has come into use in instruction, pre‐procedural arranging, in‐procedural representation, and the adoption of healthy lifestyle behaviors after the diagnosis of CVDs (Singla & Senthil Kumar, 2019). A relatively new technology, VR is now also used in cardiac rehabilitation programs to improve health behavior and clinical outcomes, motivation, and commitment (García‐Bravo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%